Beyond tourism: exploring export sector contributions to Bali’s regional economy - Afrizal Fajri; Rahmad Rido Yupito; Yustine Juneytalenta; Alief Al Labiib Chaylendra; Novitri Nur Zahra (Jurnal Pariwisata Pesona, 2026)
Bali’s economy has long been synonymous with tourism, yet recent global disruptions have exposed the region’s vulnerability to external shocks. This study investigates the contribution of the export sector to Bali’s regional economic performance, positioning it as a potential driver of growth beyond tourism. Drawing on the theoretical framework of Export-Led Growth (ELG), the research aims to assess whether export expansion significantly influences the island’s Gross Regional Domestic Product (GRDP). Using a mixed-method approach, the study employs secondary time-series data from the Bali Provincial Statistics Agency (BPS) covering the period 2015–2024. A simple linear regression analysis was conducted using SPSS 26, with GRDP as the dependent variable and export value as the independent variable. The model produced a strong correlation (R = 0.759) and a coefficient of determination (R² = 0.577), indicating that exports explain approximately 57.7% of the variation in GRDP, with the regression coefficient being statistically significant (p = 0.011). The findings confirm that exports have a positive and significant effect on Bali’s economic growth, providing empirical support for the ELG hypothesis at the regional level. The results underscore that export diversification particularly in high-value sectors such as fisheries, textiles, and agricultural products can serve as a stabilizing mechanism amid the volatility of global tourism. The study further highlights that policy interventions focusing on digitalization, logistics infrastructure, and SME capacity building are critical to sustaining export-led regional development.